The two sides of migration in Central America: Distributional impacts in Guatemala - Escalante, Luis Enrique; Aragie, Emerta A.; Hernandez, Manuel A. (International Food Policy Research Institute, 2025)
International migration has become a defining force shaping Guatemala’s economy, with both outflows and return inflows generating diverse impacts across economic sectors, labor markets, and household welfare. This study quantifies the economy-wide and distributional impacts of these migration dynamics using a modeling framework that integrates detailed microdata on migration profiles. Three scenarios are considered: a reference case reflecting recent-historical migration patterns (MIG-0), moderately restricted migration (MIG-1), and net return migration (MIG-2), capturing newly emerging shifts in emigration and return flows by skill level within the country. Results reveal trade-offs between aggregate economic performance and distributional impacts across households. Compared to a baseline economy with no mobility, Gross Domestic Product (GDP) rises modestly under the reference scenario (+0.2%) and by an additional 0.3-0.5 percentage points under the more restrictive cases, driven by higher labor availability from returnees and currency depreciation. Non-agro-processing manufacturing shows the largest expansion (up to 1.8%), reflecting its strong labor-absorption potential. Household welfare, however, is highly sensitive to remittance flows, with income and consumption declining under the restrictive scenarios. These findings underscore the need for policies that facilitate returnee reintegration and strengthen social protection for remittance-dependent households, ensuring that the macroeconomic gains from migration adjustments translate into equitable welfare improvements.